Mögliche Anforderungen an ein LMS aus Bibliothekssicht - Martin Roos (FernUniversität Hagen, 2021)
Library services are essential for teaching. These services should be better integrated as part of a redesign of an LMS. This applies to both the catalogs, databases and media provided by the library, as well as the possibilities of literature and information management. If you look beyond the library to other areas of the economy, the question arises to what extent you can learn from other industries. In various economic sectors, the customer relationship is maintained and intensified via the customer account. Particularly noteworthy are the customer accounts of banks and insurance companies. The online bank account offers a variety of functions that are relevant to the customer relationship. These can serve as a model for integrating the library into an LMS. The involvement of librarians to support literature research is also useful.